High ionisation absorption in low mass X‐ray binaries. Issue 4 (May 2016) - Ponti, G.; Bianchi, S.; Muñoz‐Darias, T.; De, K.; Fender, R.; Merloni, A.
Abstract: The advent of the new generation of X‐ray telescopes yielded a significant step forward in our understanding of ionised absorption generated in the accretion discs of X‐ray binaries. It has become evident that these relatively weak and narrow absorption features, sporadically present in the X‐ray spectra of some systems, are actually the signature of equatorial outflows, which might carry away more matter than that being accreted. Therefore, they play a major role in the accretion phenomenon. These outflows (or ionised atmospheres) are ubiquitous during the softer states but absent during the powerlaw dominated, hard states, suggesting a strong link with the state of the inner accretion disc, presence of the radio‐jet and the properties of the central source. Here, we discuss the current understanding of this field. (© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)